Dentinal crack formation after different obturation techniques - Hale Ari Aydinbelge; Nazife Tugba Azmaz; Mine Ozcelik Yilmaz (Wolters Kluwer Medknow Publications, 2019)
Introduction: The aim of this investigation was to compare the incidence of dentinal crack after different obturation techniques. Materials and Methods: Fifty-five mandibular teeth with mature apices and straight root canals (>5°) that had been extracted for periodontal reasons were selected and stored in distilled water until use. The teeth were randomly assigned to five groups of 15 teeth each. The groups were as follows; (Group 1) no canal preparation, (Group 2) canal preparation, (Group 3) canal preparation and obturation with cold lateral condensation technique, (Group 4) canal preparation and obturation with warm vertical condensation (WVC) technique, and (Group 5) canal preparation and obturation with single-cone (SC) technique. Afterward, the teeth were horizontally sectioned at 3, 6, and 9 mm from the apex with a low-speed saw under water cooling. All slices were then viewed through a stereomicroscope at ×25 magnification and pictures were taken. The presence of dentinal crack was noted and analyzed using the Chi-square test. Results: The Group 1 had no dentinal crack. All the other groups resulted in dentinal crack. Groups 3 and 4 produced significantly more dentinal crack than the other groups in the 6 and 9 mm sections (P < 0.05). The Groups 3 and 4 produced significantly more dentinal crack in the 6 and 9 mm sections than 3 mm sections (P < 0.05). Conclusion: Under the conditions of this study, after root canal filling with the cold lateral and WVC techniques determined more dentinal cracks than the only preparation and SC technique. The SC technique seems to be an appropriate obturation technique.